NUTRITIONAL CONDITIONS OF PHYSICAL DEFICIENTS ATTENDANTS OF THE MOTOR ACTIVITIES FOR DISABLED PEOPLE PROGRAM (Fiep Bulletin - online, 2014)
Although there are many researches related to nutritional status of different populations, there are very few papers about nutritional aspects for disabled people. This work had as objective to describe the nutritional conditions of physically disabilities through anthropometric measurements and investigation of their alimentary habits. It was conducted over a sample of 10 men, physically disabled, from the Wheelchair Basketball Team of the Motor Activities for Deficients Program, from the Federal University of Amazon who have paraplegia, inferior members amputation and paralytic poliomyelitis. In the dietary evaluation, it was used the alimentary register of three days to verify the energy, macronutrients and cholesterol consumption. The anthropometric measurements taken were weight, height, waist and hip circumferences, and cutaneous folds. The amputated ones presented homogeneity in the weight, overweight in relation to BMI and high value for waist circumference, in a level considered as increased risk for cardiovascular complications. The paraplegic ones presented heterogeneity in the weight and BMI of obesity, although the average for waist circumference was not considered in a level of risk for cardiovascular complications. The one who had paralytic polio presented a high degree of BMI and waist circumference, with increased risk for cardiovascular complications. In relation to the dietary evaluation, the results of energy and macronutrients consumption demonstrated a great heterogeneity of the sample, both from an individual to the other as for the same individual from one day to another, presenting on average an energy consumption of 2448 kcal, with 74g of lipids (27%), 123g of proteins (20%) and low percentage of carbohydrate (53%). The average cholesterol consumption was above the recommendation of 300mg per day. More studies are necessary in relation to nutritional aspects of physically disabled people, aiming a better nutritional characterization of this population, contributing for a better life quality for these individuals.
Keywords: Disabled people; alimentary habits; anthropometric measures